Appropriate Professional Education Helps In Making Better Human Capital In An Aspirant Of A good Career - Arpita Ghosal; R.P. Banerjee; Sanchita Saha (Program Studi Ekonomi Syariah, Fakultas Ekonomi dan Bisnis Islam, Universitas Al Hikmah Indonesia, 2023)
Professional education has twin focus: On one hand it aims at creating a good basis of earning livelihood to the level of happiness of the person and on the other hand, it attempts to contribute directly or indirectly to the economic well-being Es of the nations. Whereas, there are plethora of professional courses of study, only a few are there which can fulfil the short term objective of the person and finally contributes to the effective making of an enduring and ever growing worth of the human capital in the person. Management education in the right forum thus enables the person to develop that effective and enduring career. It is in the backdrop study of management from right place creates a sustainable and valued career. This study is aiming to explore that how professional courses help an individual to attain a successful career. Every individual has their own economical and social responsibilities towards their society and country. Proper selection of career is one of the most important decisions in individual’s life. Now-a-days professional courses are playing an important role to make corporate employees. Many professional courses are now available in education world. So the selection of a professional course is very important. An individual must select the professional course on the basis of the area of interest, scope in the particular sector, eligibility of the individual. Through a professional course an individual gets professional orientation and professional orientation of career enables a young aspirant develop a better footing in life and activities. It also enhances the speed and volume of growth of corporate in terms of socio economic context. In this study we are going to explore from every aspect that how professionalism in career and work effectively induces the spirit of internationalism in given context.